Unveiling the hidden burden: Exploring the psychosocial impact of cutaneous leishmaniasis lesions and scars in southern Ethiopia. - Behailu Merdekios; Misgun Shewangizaw; Abebayehu Sappo; Eshetu Ewunetu; Johan van Griensven; Jean-Pierre van Geertruyden; Melissa Ceuterick; Hilde Bastiaens (PLoS ONE)
Background Cutaneous leishmaniasis (CL) poses a major public health concern in Ethiopia, with lesions and scars commonly affecting exposed body parts, resulting in physical, social, and psychological consequences. This study aims to assess the psychosocial impacts of CL, shedding light on the experiences and perceptions of affected individuals, thus contributing to the knowledge on Cutaneous leishmaniasis in Ethiopia and informing public health interventions to address its psychosocial effects. Methods Using a descriptive phenomenological design, the study explored the lived experiences of individuals with Cutaneous leishmaniasis lesions and scars. Participants were purposively selected, and data was collected through open-ended in-depth interviews. The analysis combined inductive and deductive approaches through an iterative process, developing a coding framework with seven themes (lesion & CL scar each) and subthemes, resulting in giving important insights in the psychosocial impacts of CL. NVivo 12v supported the analysis process. Result The study unveiled negative views and misconceptions surrounding CL and its impact. Application of traditional herbal medicine for CL lesions often leads to pus formation and a foul odour, triggering negative attitudes from others, resulting in embarrassment, pain, and anxiety, leading to discomfort and isolation. The negative psychosocial attitudes associated with CL scars deeply impacted affected individuals, influencing their behaviour. This included isolation and absenteeism from school. CL scars served as unique identifiers, shaping the affected individuals' identity and self-perception. The unreceptive environment affected the participant's self-esteem and coping mechanisms. The negative impact of CL scars extended to role performance, marriage prospects, and overall happiness, particularly for females facing additional societal pressure and stigma. Conclusion The study highlights the need for improved education and awareness about CL to reduce misconceptions and negative attitudes towards affected individuals. Additionally, more effective treatment options and integrated preventive ways should be explored to minimize the physical and psychological impact of CL on affected individuals.